2018
DOI: 10.1002/mnfr.201800303
|View full text |Cite
|
Sign up to set email alerts
|

Oral Immunotherapy with a Phosphorylated Hypoallergenic Allergen Ameliorates Allergic Responses More Effectively Than Intact Allergen in a Murine Model of Buckwheat Allergy

Abstract: These results indicate that attenuated allergens can suppress Th2-induced allergic responses via induction of Tfh cells, which are regulated by IL-6 secreted from dendritic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The most frequently used adjuvants for the establishment of food allergy models are cholera toxin (CT, [17,44,45,46]), staphylococcus enterotoxin B (SEB, [47]), aluminium hydroxide (alum, [41,48,49]), and lipopolysaccharide (LPS, [50]).…”
Section: Usage Of Adjuvants In Food Allergy Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently used adjuvants for the establishment of food allergy models are cholera toxin (CT, [17,44,45,46]), staphylococcus enterotoxin B (SEB, [47]), aluminium hydroxide (alum, [41,48,49]), and lipopolysaccharide (LPS, [50]).…”
Section: Usage Of Adjuvants In Food Allergy Mouse Modelsmentioning
confidence: 99%
“…In their hands only the lower allergen dose (5 mg extract), but not the higher dose (25 mg extract) was able to successfully induce allergic sensitization [40]. Moreover, Li et al defined a symptom score for the evaluation of the induced allergic reactions (Table 2) which has proven very useful and thus has been frequently used for other food allergy models [17,49,50,69,70,71].…”
Section: Types Of Mouse Food Allergy Modelsmentioning
confidence: 99%
“…So far, various mouse food allergy models have been established, which lays a foundation for the evaluation of food allergens, the mechanism study of immune responses, and the development of AIT. 31,32 In this research, the allergenicity of mtTM and mtMLC was evaluated in vivo using the Balb/c mouse models. The gut is the main organ involved in nutrient and water uptake, and also it was a basic barrier against harmful substances and pathogens from the external environment.…”
Section: Food and Function Papermentioning
confidence: 99%
“…On the other hand, the mutation of some of the cysteine residues affected the pepsin digestibility and IgEbinding activity (Satoh et al 2008). Moreover, Katayama et al (2018) indicated that the phosphorylated Fag e 2 can induce stronger and safer desensitisation than intact Fag e 2.…”
Section: Reducing the Amount Of Buckwheat Allergens In Foods And Prodmentioning
confidence: 99%